Thea Stilton and the Chocolate Sabotage - Thea Stilton & Geronimo Stilton
Join Thea Stilton and the Thea Sisters on an adventure packed with mystery and friendship! The Thea Sisters are visiting a friend in Ecuador who has a sweet job -- he runs a chocolate factory! His factory is in the running for a major award for its environmental methods. But suddenly, chocolate production starts to malfunction. Is it sabotage? It's up to the Thea Sisters to solve this mouthwatering mystery!